Sectoral Growth Dynamics: Inequality Tradeoff and Sustainability in Central America - Manuel Antonio Vanegas Sr (Revista de Fomento Social)
This study is concerned with both the interlinks between inequality, extreme poverty reduction, and economic growth and estimates the dampening impact on economic growth and on extreme poverty rates using the Central American countries annualized level data. These dynamic complexities, are analyzed within the auto regressive distributed lag bounds testing approach to cointegration. The results show that when extreme poverty reduction is decomposed into two separate impacts, the growth impact on poverty reduction was lessened by the incidence of high-income inequality. The total dampening impact of inequality, varies from 1.1522% for El Salvador to 2.0589% for Honduras, due to a 1% increase in inequality. Reducing inequalities can be doubly beneficial for the extreme poor in Central American countries. The magnitude of changes in poverty reduction depends on each country-specifics, which leads to the implementation of a different strategy for extreme poverty reduction to different countries